G. L. Castelli, principe di Torremuzza, numismatico ed antichista ad Halaesa Archonidea (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
G. L. Castelli (1727-1792), Prince of Torremuzza, was one of the most important leaders of the Sicilian study of antiquity in 18th century. This article analyzes the research activity by Castelli, interested in the coinage and archaeological evidences of Halaesa Archonidea, nowadays identified near Tusa (ME). An analysis of Castelli’s studies about these issues is here proposed, critically evaluating their importance according to the standards of antiquarianism. It’s certainly emerged the profile of a classical scholar with wide-ranging interests, to be considered the founder of the numismatic and archaeological modern studies on ancient Halaesa.
Keywords: antiquarianism; Castelli; coinage; Halaesa; numismatic; study of antiquity; Torremuzza; Tusa